Environmentally assisted fatigue in LWR - Development of a calculation tool - Skoglund, Annelie (My University, 2021)
The ASME Boiler and Pressure Vessel Code [1] provide rules for the design and construction of class 1 nuclear power plant components. Current design of fatigue curves is based primarily on straincontrolled fatigue tests of small polished samples at room temperature in air but recent data from the USA and Japan demonstrate that the light water reactor (LWR) coolant has significant effects on the fatigue resistance of materials. The Nuclear Regularity Commission (NRC) has written a report, NUREG/CR-6909 [2] that reviews and quantifies these effects on fatigue life of typical reactor materials and proposes a method for establishing reference curves and environmental fatigue correction factors for evaluating fatigue life. The purpose of this project is to use the proposed influence in fatigue life, due to the environmental parameters, such as temperature, rate of strain, dissolved-oxygen and amount of sulphide in the LWR coolant environment, according to the NRC report [2] to calculate the environmental fatigue correction factor. If the fatigue correction factor becomes larger than 1, the fatigue usage factor will decrease. The fatigue usage factor is the number of cycles of a certain load divided by the total number of allowable cycles of the same load. In other words, if the fatigue correction factor is larger than 1, for example 2, the number of allowable cycles will decrease to half of the previous number of allowable cycles, i.e., the fatigue life of the specimen will decrease. The research is performed using the software ANSYS Mechanical Workbench [3] and PIPESTRESS [4]. In ANSYS an axisymmetric 2-dimensional model of a pipe is constructed. The load set is one single thermal transient which will, together with convection at surfaces cause a temperature distribution over time over the whole domain. This temperature distribution in turn will cause strains in the material. The strain rates and the temperature changes are then used to calculate the fatigue correction factor. The report contains the results of the fatigue corrections factors calculated for a single common thermal transient with different ramp times of the temperature load. The load is applied on a straight pipe with different thicknesses of a common reactor material. The results from ANSYS and PIPESTRESS are then compared. When studying a temperature decrease of the coolant from 290℃ to 20℃ it can clearly be seen that the fatigue correction factor increases when the thickness of the pipe increases in both PIPESTRESS and ANSYS but the values are always slightly lower in ANSYS. The result differs between the software when studying the ramping time dependence. In PIPESTRESS the worst scenario appears for the thicker pipes when the temperature is down to 20℃ in 10 seconds while 1 second is worse for the two thinner ones. In ANSYS on the other hand the worst case is 1 second ramping time no matter thickness except for 60 mm when 10 seconds is worse.
Keywords: ANSYS Mechanical Workbench; ASME; NUREG; PIPESTRESS; LWR; fatigue correction factor; fatigue usage factor